Shear strength characteristics of a compacted kaolin under infiltration conditions - Inge Meilani. (2008)
This thesis consists of 3 parts. Study the shear strength characteristics of saturated and unsaturated soils under shearing-infiltration conditions. The characteristics of pore-water pressure development and volume change in soil under infiltration were investigated.